2008
DOI: 10.1243/09544070jauto824
|View full text |Cite
|
Sign up to set email alerts
|

Classification and analysis of lateral torque-vectoring differentials using velocity diagrams

Abstract: This paper describes the classification and analysis of lateral torque-vectoring differentials using velocity diagrams, which are frequently used for the gear-shifting analysis of an automatic transmission. A lateral torque-vectoring differential is composed of the mechanism of torque vectoring from the right wheel to the left wheel, and the similar mechanism of torque vectoring from the left to the right. The analysis shows that, when only the mechanism part of one-way torque vectoring is considered, then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…where K cvt is the gain value of the CVT ratio and the referenced CVT ratios are related to the steering angle. Also the gain values K cvt in both equation (12) and equation (13) are selected to be equal in order to maintain the symmetry of the driving behaviour of the vehicle. While cornering, a higher ratio slows the inside wheel, and a lower ratio speeds up the outside wheel to achieve the limited-slip differential function.…”
Section: Dual Continuously Variable Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…where K cvt is the gain value of the CVT ratio and the referenced CVT ratios are related to the steering angle. Also the gain values K cvt in both equation (12) and equation (13) are selected to be equal in order to maintain the symmetry of the driving behaviour of the vehicle. While cornering, a higher ratio slows the inside wheel, and a lower ratio speeds up the outside wheel to achieve the limited-slip differential function.…”
Section: Dual Continuously Variable Transmissionmentioning
confidence: 99%
“…Mitsubishi S-AWC, Honda SH-AWD and ZF Torque Vectoring). Studies of the dynamics and control logic of TVDs have been previously reported, [3][4][5][6][7][8][9][10][11][12][13][14] and the principles of operation have already been explained in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The TVD's theoretical energy loss E LOSS , which is generated by the slip clutch when a vehicle drives with S, is represented as [17] …”
Section: Maximum Acceptable Differential Speed Ratio Of Torque-vectormentioning
confidence: 99%
“…Because of its complicated structure, the operation and characteristics of these mechanisms are difficult to understand. Therefore, the present authors evaluated the characteristics, namely the output torques of the right and the left wheels, the clutch torque required to generate the output torque difference, the clutch slip speed, and the energy loss of TVD by applying the velocity diagram and concluded that TVDs are classified into seven kinds in total and that the TVD mechanisms adopted in the super AYC [15] are well balanced to reduce both the required clutch torque and the clutch slip speed [17]. In that analysis, the maximum acceptable differential speed ratio S max , which is defined as the differential speed ratio of TVD in the state when the differential speed of the slip clutch becomes zero, is introduced as a design parameter of the TVD.…”
Section: Introductionmentioning
confidence: 99%
“…14 The application of a velocity diagram to a TVD was proposed by Sawase and Inoue. 15 The velocity diagram can easily represent the revolution speed and the torque relation of each gear, and then we can clearly understand the characteristics of the TVD. First, the definitions of the E-TVD in this paper are described.…”
Section: Introductionmentioning
confidence: 99%